Proprotein Convertase Subtilisin-Kexin type-9 (PCSK9) and triglyceride-rich lipoprotein metabolism: Facts and gaps - Baragetti, A.; Grejtakova, D.; Casula, M.; Olmastroni, E.; Jotti, G.; Norata, Giuseppe; Catapano, A.; Bellosta, S. (Academic Press, 2018)
After more than a decade of intense investigation, Pro-protein Convertase Subtilisin-Kexin type 9 (PCSK9) remains a hot topic of research both at experimental and clinical level. Interestingly PCSK9 is expressed in different tissues suggesting the existence of additional function(s) beyond the modulation of the Low-Density Lipoprotein (LDL) receptor in the liver. Emerging data suggest that PCSK9 might play a role in the modulation of triglyceride-rich lipoprotein (TGRL) metabolism, mainly Very Low-Density Lipoproteins (VLDL) and their remnants. In vitro, PCSK9 affects TGRLs production by intestinal cells as well as the catabolism of LDL receptor homologous and non-homologous targets such as VLDL receptor, CD36 and ApoE2R. However, the in vivo relevance of these findings is still debated. This review aims at critically discussing the role of PCSK9 on TGRLs metabolism with a major focus on the impact of its genetic and pharmacological modulation on circulating lipids and lipoproteins beyond LDL.